Job Satisfaction of Government Agriculture Officers Working in the Extension Service of Nepal - Pun, Min Bahadur; Timilsina, Ram Hari; Joshi, Narayan Raj; Sigdel, Udit Prasad (Journal of Agriculture and Environment, 2023)
A study was conducted to assess the job satisfaction status of government agriculture officers working in the extension service of Nepal and to find out the significant satisfaction determining factors as perceived by them. Semi-structured questionnaire was applied via online Google forms and findings were drawn from 112 responses. 64.29% respondents perceived their overall job satisfaction to be neutral. Regarding the individual factors, they were found to be satisfied with four factors, namely; Physical facilities at the office, Guidance of/and relationship with supervisors/office chief, Cooperation of/and relationship with co-workers and welfare/retirement facility, but dissatisfied with capacity building and job promotion opportunity while neutral to pay factor. Regarding the most preferred attribute of job satisfaction, capacity building and job promotion opportunity ranked first. Guidance of/and relationship with supervisors/office chief and Pay factor ranked second and third respectively. 52.63% of the respondents working in central or policy level offices were found to be with less workload than they expect. 54.5% of respondents expressed having unfair practices in case of various opportunities within the organization. There should be enough and effective capacity enhancement opportunities and the concerned organization should foster a fair system to make them happy and productive manpower of the country.